The Benefits of Using Facebook Live for Listening Activities in A Korean University EFL Classroom - Kobylinski, Chris (International Journal of Educational Technology and Learning, 2018)
Although the methods and mediums of receiving information have rapidly changed, the main method of presenting listening activities in an English as a Foreign Language (EFL) classroom has not. More and more people are using social networking services (SNSs) as their source for daily information, yet most EFL classrooms still use voice only recordings for listening activities. To keep up with the changes and to provide students with real authentic listening experiences, many teachers have begun to use SNSs in their classrooms. This paper examines the strengths and weaknesses of using Facebook Live as an authentic source for listening activities in an EFL classroom. The data collected revealed a variety of strengths and weaknesses of this application, and showed potential for use within the classroom and for allowing students to practice listening outside the classroom.